Non-neoplastic findings in colon capsule endoscopy: Additional yield - Eskemose, Sebastian Radic; Kaalby, Lasse; Deding, Ulrik; Koulaouzidis, Anastasios; Bjørsum-Meyer, Thomas (Endoscopy International Open, 2024)
Background and study aims Despite the common occurrence of non-neoplastic findings (NNFs) in individuals with a positive fecal immunochemical test (FIT), few studies have reported on these findings. The aim of this cross-sectional study was to determine the prevalence of colonic NNFs in three cohorts of Danish clinical trial participants who underwent colon capsule endoscopy (CCE).Patients and methods Retrospectively collecting NNFs from CCE reports of three Danish trials, we classified them into five categories: diverticula, vascular abnormalities, inflammation, erosions/ulcerations, and others. The statistical analysis included 516 participants from three trials, with a mean age ranging from 59.2 to 63.9 years. The participants in the three trials were FIT-positive screening or symptomatic individuals.Results NNFs were reported in more than half of the CCE procedures (50.6% to 77.9%), with colonic diverticula being the most common NNF appearing in 40.9% to 66.9% of the CCE reports. Vascular abnormalities and erosions/ulcerations were also common depending on the specific trial.Conclusions NNFs are common and may be an indicator of more widespread disease. Furthermore, NNFs may develop into clinically significant conditions despite their benign appearance. This paper expands on the limited literature about prevalence of NNFs and underscores the additional value of CCE video recordings beyond detecting polyps.
Keywords: Endoscopy Lower GI Tract; Polyps / adenomas / ...; CRC screening; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE...); Lower GI bleeding